2020
DOI: 10.1101/2020.08.28.268599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unraveling Endothelial Cell Phenotypic Regulation By Spatial Hemodynamic Flows With Microfluidics

Abstract: Human endothelial cells (hECs) experience complex spatiotemporal hemodynamic flows and that directly regulate hEC function and susceptibility to cardiovascular disease. Recent medical imaging studies reveal that helical flows strongly correlate with lowered disease susceptibility, as contrasted to multidirectional disturbed flows. However, a lack of platforms to replicate these spatial profiles of flow (SPF) has prevented biological studies to investigate the role hECs play in tuning the observed SPF-correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Staggered herringbone structures have primarily been designed and used for improved mixing in microfluidics, [38] and only a few studies have used this structure to generate different flows for cell culture. [39] A study by Levesque et al showed that by changing vascular geometry, the morphology and shear stress of the aortic endothelial cells can be altered. [60] Although attributing the morphological changes only to flow is challenging, our microfluidic device simulating atherogenic flow conditions shows that similar morphological changes can be achieved in vitro by exposing cells to different flow regimes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staggered herringbone structures have primarily been designed and used for improved mixing in microfluidics, [38] and only a few studies have used this structure to generate different flows for cell culture. [39] A study by Levesque et al showed that by changing vascular geometry, the morphology and shear stress of the aortic endothelial cells can be altered. [60] Although attributing the morphological changes only to flow is challenging, our microfluidic device simulating atherogenic flow conditions shows that similar morphological changes can be achieved in vitro by exposing cells to different flow regimes.…”
Section: Discussionmentioning
confidence: 99%
“…To simulate these more realistic conditions, we adapted a microfluidic flow chamber/mixer that permitted laminar and chaotic flow, to induce cells to adopt elongated and non-elongated phenotypes, respectively. [38,39] In this microfluidic system the middle part of the chip uses a herringbone pattern on the channel ceilings that works as a mixer and creates chaotic flow profiles (Figure 6b and Figure S5a, Supporting Information) similar to the disturbed laminar flows found in atheroprone areas of the vasculature. To assess the flow patterns, we perfused 10 μm fluorescent beads and showed that the beads' trajectories were consistent with both laminar and chaotic flows (Figure 6b).…”
Section: Uptake Of Nps Correlates With Cell Morphology In An Atheroge...mentioning
confidence: 99%